The Oxford handbook of health economics - Glied, Sherry; Smith, Peter (Peter C.) (Oxford : Oxford University Press, 2011)
This handbook provides an engaging, comprehensive review of health economics, with a focus on policy implications in the developed and developing world. Authoritative, but non-technical, it stresses the wide reach of the discipline - across nations, health systems and areas within health and medical care.
Description based on print version record.
Includes bibliographical references and index.
Keywords: Medical economics; Medical policy